1984
DOI: 10.1139/m84-167
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide production from nitrification and denitrification in marine sediment at low oxygen concentrations

Abstract: Measurements of N2O production (release of free N2O), nitrification, and denitrification were made simultaneously in NH4Cl- and KNO3-amended suspensions of marine sediment. An open flow system was designed for the application of low partial pressures of O2 (0–10 kPa) to the sediment. The overall rate of N2O production increased dramatically at the lowest O2 tensions (0–0.2 kPa) and had a maximum at complete anoxia. The specific rates of N2O production from nitrification (N2On) and from denitrification (N2Od) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(50 citation statements)
references
References 12 publications
2
48
0
Order By: Relevance
“…from ammonium. This conclusion is further corroborated by the observed hypoxic conditions during large parts of all tides, as concentrations of O 2 have been clearly recognized as the key control on N 2 O production by both nitrification and denitrification, especially during high nutrient availability (e.g., Goreau et al 1980;Jørgensen et al 1984;de Bie et al 2002).…”
Section: Discussionmentioning
confidence: 69%
“…from ammonium. This conclusion is further corroborated by the observed hypoxic conditions during large parts of all tides, as concentrations of O 2 have been clearly recognized as the key control on N 2 O production by both nitrification and denitrification, especially during high nutrient availability (e.g., Goreau et al 1980;Jørgensen et al 1984;de Bie et al 2002).…”
Section: Discussionmentioning
confidence: 69%
“…In the estuarine sediments, N 2 O is produced from microbial nitrogen transformations. Generally, three microbial processes can lead to N 2 O production: denitrification (15,22), nitrification (12,15,34,50), and dissimilatory nitrate reduction to ammonium (44). Any factors which affect these processes would indirectly affect N 2 O production (9,17).…”
Section: Discussionmentioning
confidence: 99%
“…1) in the ridge as it did in the runnel (Table 2). The specific role of O2 on the nitrification is difficult to assess: It was found earlier that the microbial oxidation of NH,' stops at O2 concentrations between 1.1 and 6.2 pM (Jsrgensen et al 1984) and that the process is inhibited between 2 to 3 times air saturation in a n estuarine environment (Henriksen & Kemp 1988). Kemp et al (1990) found that nitrification was absent when O2 concentrations in the overlying water declined below 125 pM and sediments were anoxic.…”
Section: Resultsmentioning
confidence: 99%